The new function for f(x) = (x – 3) is g(x) = x/2 – 3
Given,
The function, f(x) = (x – 3)
Horizontal stretch by a factor of 2
The quadratic parent function f(x) = (x – 3) is the simplest form of a quadratic function.
If the function is multiplied by the factor b and:
|b| > 0 the function is stretched.
If 0 < |b| < 1 the function is compressed.
Then the new function will be in the form:
g(x) = (1/b)x - 3
Therefore, keeping the above on mind, if b=2, then the new function is:
g(x) = (1/2)x - 3
g(x) = x/2 - 3
Learn more about functions here:
https://brainly.com/question/12364209
#SPJ1